2013
DOI: 10.3390/ijms14036345
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Skeletal Growth in Adolescent Idiopathic Scoliosis Is Associated with Abnormal Quantitative Expression of Melatonin Receptor, MT2

Abstract: The defect of the melatonin signaling pathway has been proposed to be one of the key etiopathogenic factors in adolescent idiopathic scoliosis (AIS). A previous report showed that melatonin receptor, MT2, was undetectable in some AIS girls. The present study aimed to investigate whether the abnormal MT2 expression in AIS is quantitative or qualitative. Cultured osteoblasts were obtained from 41 AIS girls and nine normal controls. Semi-quantification of protein expression by Western blot and mRNA expression by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…In osteoblasts from girls with AIS, an abnormal expression of MT2 receptor has been observed, and the expression was not demonstrable in four out of the eleven girls [ 25 ]. Furthermore, AIS patients with a low level of expression of MT2 receptor in osteoblasts showed a longer arm span than those with a normal expression level of MT2 receptor [ 34 ]. Hence, a comprehensive investigation on the MT2 receptor including the expression of RNA and protein, the structure of DNA and protein, and the coupling between MT2 receptor and Gi/Gs proteins should be carried out in GPCs from AIS subjects and control subjects to facilitate further understanding of the abnormalities in the MT2 receptor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In osteoblasts from girls with AIS, an abnormal expression of MT2 receptor has been observed, and the expression was not demonstrable in four out of the eleven girls [ 25 ]. Furthermore, AIS patients with a low level of expression of MT2 receptor in osteoblasts showed a longer arm span than those with a normal expression level of MT2 receptor [ 34 ]. Hence, a comprehensive investigation on the MT2 receptor including the expression of RNA and protein, the structure of DNA and protein, and the coupling between MT2 receptor and Gi/Gs proteins should be carried out in GPCs from AIS subjects and control subjects to facilitate further understanding of the abnormalities in the MT2 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Man et al [ 24 ] noted that melatonin failed to promote both proliferation and differentiation of osteoblasts from AIS subjects, which might contribute to the low bone mineral density in these patients [ 41 , 42 , 43 , 44 ]. This abnormality of melatonin could be attributed to the abnormal expression of MT2 receptor [ 25 , 34 ]. Taking these observations together, it is likely that melatonin signaling pathway dysfunction could be a systemic problem and plays an important role in the abnormal systemic bone growth in AIS subjects [ 4 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…These same genes play an essential role in regulating osteoblastogenesis and osteoblast function, bone mineralization, and ossification . In keeping with this, a disruption in melatonin‐mediated signaling, whether it be through a suppression of nocturnal melatonin levels by light at night (LAN) or through impaired melatonin receptor signaling in osteoblasts, is thought to underlie, respectively, the increased risk of hip and wrist fracture and low BMD in shift workers and to the development of adolescent idiopathic scoliosis . Decreases in melatonin have been shown to alter bone morphology in various models including fish , chickens , and mice .…”
Section: Melatonin and Bonementioning
confidence: 99%
“…The increase in bone mass was also observed after administration of melatonin in vivo [ 65 , 66 , 67 ]. In our studies, it was found that osteoblasts cultured from human AIS patients failed to respond normally to melatonin challenge at various doses with regard to proliferation and differentiation [ 68 , 69 , 70 ] in contrast to that of the normal controls. Despite this well-known clinical manifestation of AIS, its pathogenesis and relationship to premature osteoporosis remain unresolved.…”
Section: Discussionmentioning
confidence: 90%